The Effect of Complementary Acupressure Therapy on Nausea and Vomiting After Regional Block Anesthesia (Spinal Anesthesia) in the Recovery Room Imelda Indonesian Workers General Hospital, Medan - Satriani Hartalina Gultom; Candra Meriani Damanik; Yuni Shanti Ritonga; Syahrul Handoko Nainggolan; Ali Asman Harahap (International Journal of Health and Medicine, 2024)
Postoperative nausea and vomiting is one of the side effects that often occurs in spinal anesthesia. Nausea and vomiting affect patient morbidity such as stress, discomfort, dehydration, prolonging treatment time and increasing treatment costs. This study aims to determine the effect of acupressure therapy on the incidence of nausea and vomiting after spinal anesthesia in the recovery room at the Imelda Workers Indonesia General Hospital, Medan. This type of research is quantitative research with quasi-experimental research methods. Data reports in the province of North Sumatra showed that there were 25,602 patients who underwent surgery. Meanwhile, at the Indonesian Umim Workers Hospital in Medan, data on surgical patients for January-March 2024 totaled 666 patients, and 250 patients had spinal anesthesia. This research was carried out in February - June 2024 at the Imelda Indonesian Workers General Hospital, Medan. The research sample was taken as many as 20 respondents. incidence of nausea and vomiting after spinal anesthesia at the Imelda Workers Indonesia General Hospital, Medan. Based on the characteristics of respondents based on age, they were in the age range of 36-40 years, namely 55%, based on gender, the majority of respondents were women, namely 60%, respondents based on smoking history were the majority 65%, the distribution of respondents with a history of nausea and vomiting was the majority 55% and the majority of respondents with nausea and vomiting were 60%. The recommendation for this research is that acupressure therapy can be applied in nursing practice so that patients are able to perform it independently. For the Imelda Workers Indonesia General Hospital, Medan, it is necessary to score the risk of nausea and vomiting in patients before surgery to minimize the incidence of post-operative nausea and vomiting.